Using scaffolds to support preservice teachers’ reflective practice - Chaseley, Tina L.; Abercrombie, Sara (Frontiers in Education, 2025)
IntroductionThe primary purpose of this study was to examine the impact of various types of reflection prompt scaffolds on preservice teachers’ metacognitive and problem-solving abilities.MethodsParticipants were preservice teachers in an educational technology course within an accredited teacher education program. Mixed-methods data were collected using a cycle of reflection beginning with concrete and authentic situations encountered during a simulated teaching activity and resulting in reflective observation through blogs. Two rounds of teaching and reflection occurred, with blog reflections scaffolded by two types of prompts: traditional descriptive and critical incident. Qualitative and quantitative data were analyzed separately and findings were integrated across phases and data type.ResultsResults indicated that the type of scaffold impacted ill-structured problem-solving, pedagogical reasoning processes, metacognition, and reflective thinking in various ways.DiscussionImplications for teacher education are discussed.